SYSTEMATICS OF RARE EARTH ELEMENTS, TH, HF, SC, CO, CR, AND NI IN THE VENDIAN PELITIC ROCKS OF THE SEREBRYANKA AND SYLVITSA GROUPS FROM THE WESTERN SLOPE OF THE CENTRAL URALS: A TOOL FOR MONITORING PROVENANCE COMPOSITION - Maslov A.V.; Ronkin Yu.L.; Krupenin M.T.; Petrov G.A.; Kornilova A.Yu.; Lepikhina O.P.; Popova O.Yu. (My University, 2006)
This paper presents the first data on the systematics of rare earth elements (REE), Th, Hf, Sc, Co, Cr, and Ni and the Nd model ages of fine-grained aluminosilicate clastic rocks of the Serebryanka and Sylvitsa groups of the Vendian from the Kvarkushsko-Kamennogorskii meganticlinorium (western slope of the Central Urals). It was found that the REE distribution patterns of shales and mudstones of the two groups are similar to those of the majority of post-Archean fine-grained terrigenous complexes. The presence of pelitic rocks with GdN/YbN > 2.0 in a number of Vendian levels suggests a contribution from an Archean component in the composition of the fine aluminosilicate clastic material. This is probably also indicated by the high degree of heavy REE depletion in some mudstone samples. The REE systematics allow us to suppose a heterogeneity of Vendian paleocatchments and variations in their composition with time. The eroded areas had the most mature composition in the beginning of Serebryanka. Starting from the second half of Serebryanka, mafic and/or ultramafic rocks started playing a significant role in the provenances. The rocks of the lower portion of the Serebryanka Group show TNd(DM) values of about 2.0 Ga, whereas the upper part of the section is dominated by rocks with TNd(DM) ≅ 1.77-1.73 Ga. This indicates that during the Taninskaya and Koiva time periods, fine aluminosilicate clastic material was supplied into the sedimentation region mainly from the west, from the eastern areas of the east European platform, where Archean and Early Proterozoic crystalline complexes dominated. A decrease in model ages was related to the addition of juvenile mantle material to the mature continental crust. Such processes can be illustrated by the mafic-ultramafic complexes (Dvoretskii, Shpalorezovskii, Vil-vinskii, etc.) located in the field of Vendian sedimentary sequences, which show TNd(DM) values from 824 to 707 Ma. It was concluded that the history of the formation of an Early Vendian rift in the western slope of the central Urals included only one rifting event (rather than three, as was previously supposed), which was supported by a variety of recent geological and isotope geochemical data. © Pleiades Publishing, Inc. 2006.
Keywords: rare earth elements; Serebryanka; central Urals; Archean; Vendian; Precambrian::Archean; Докембрий::Архей; Precambrian::Proterozoic::Neoproterozoic::Vendian; Докембрий::Протерозой::Неопротерозойская::Вендский